EFEK PEMANASAN AGGREGAT EPS MODIFIKASI TERHADAP KUATTEKAN BETON RINGAN PASIR BATU APUNG - Kusnadi, Kusnadi; Rauf, Ichsan; Imran, Imran (Program Studi Teknik Sipil, Universitas Khairun, 2024)
Using lightweight materials as construction materials reduces the weight of the structure, thereby reducing earthquake loads. Pumice sand is a light local material which is quite abundant on Tidore Island and has been used as a substitute for sand in making lightweight cement bricks (tela). To minimize the weight of lightweight concrete that uses pumice sand as fine aggregate, full substitution of the coarse aggregate with aggregate from EPS waste (white cork) is carried out. This effort is also made to reduce waste generation which damages the environment. The use of EPS waste to replace some or all of the aggregate in the concrete mixture reduces the weight significantly, but also causes a very large reduction in quality. To improve the quality of lightweight concrete using pumice sand and EPS waste, the EPS aggregate is modified by heating. Heating EPS aggregate aims to increase its density. This research aims to improve the quality of lightweight concrete using pumice sand and aggregate from EPS waste. EPS waste aggregate heating is carried out at varying temperatures of 100oc, 110oc, 120oc, 130oc, 140oc. The concrete mixture is made in volume measurements with a composition of 1 part cement, 2 parts pumice sand and 3 parts modified EPS aggregate with a cement water factor of 0.45. The quality tests carried out include compressive strength tests, tensile strength tests and collapse modulus tests. The test results show that the effect of heating in the process of making modified EPS aggregates increases the density value which has an impact on increasing the compressive strength value of the resulting concrete.